RGS1 stabilized by METTL3-mediated m6A modification promotes the tumorigenicity and macrophage M2 polarization in osteosarcoma - Zhizhong Liang; Yuxia Shi; Mao Wang; Liqiang Zhang (Journal of Bone Oncology)
Background: Regulators of G-protein signaling 1 (RGS1) has been reported to be involved in immune cell regulation in many cancer types. However, the specific role and mechanism in osteosarcoma (OS) progression and macrophage activation remain unclear. Methods: Levels of mRNA and protein were examined using qRT-PCR and western blotting. Transwell assay, wound healing assay, EdU assay and flow cytometry were used to investigate OS cell invasion, migration, proliferation and apoptosis. Xenografts in mice were established for in vivo assay. Macrophage M2 polarization was evaluated by detecting CD206 + macrophages by flow cytometry. ELISA analysis detected IL-6 and TGF-β1 levels. Methylated RNA immunoprecipitation assay was applied to explore the specific binding of RGS1 and METTL3 (methyltransferase-like 3). Results: RGS1 was highly expressed in OS tissues and cells. The silencing of RGS1 suppressed OS cell invasion, migration, growth and impaired immune response by inhibiting macrophage M2 polarization and M2 macrophage-mediated release of IL-10 and TGF-β1. Mechanistically, METTL3 promoted RGS1 m6A modification and stabilized its expression. METTL3 deficiency also inhibited OS cell invasion, migration, growth and macrophage M2 polarization, while these effects could be abolished by RGS1 overexpression. Besides that, IL–10 elevation induced by M2 macrophages promoted OS cell oncogenic phenotypes. Conclusion: METTL3 stabilized RGS1 mRNA in an m6A-dependent manner to promote the tumorigenicity and macrophage M2 polarization in osteosarcoma, suggesting a novel insight into the therapy of osteosarcoma.